Aclimatização de mudas micropropagadas de helicônia sob diferentes lâminas de irrigação, tipos e volumes de substrato - Rocha, Eliana Lee Jorge (2007)
The helicônias are ornamental plants that, with its beauty and exotics, constitute one of the biggest deversity of our flora. Exuberant, colorful , with unusual forms, they are appreciated in the international market also for its durability an d the capacity of, exactly alone, to generate surprising compositions. In result of the high dema nd of the consuming market, the culture is produced in commercial scale by means of the microp ropagation, one important technique that presents diverse stages. The stage of acclimat ization is the most important and critical phase, responsible for the high rate of mortality, low rates growth taxes and low uniformity of plants, resulting in fall production. This situatio n occurs due to few information about of the culture management in this stage. Considering that this technique is very recent in Brazil, studies are being conducted to establish the best c ombinations among different substratum, irrigation depth and types of containers. Then, as result is aclimatized plants not being supplied in all its necessities, leading to a consi derable losses and/or cutting uniform less. To minimize this problem and forces the requirements o f the consuming market, is necessary looking for scientific techniques informatives abou t the culture management. The present work had as objective to evaluate the effect of dis tinct types and volumes of substratum and different irrigation depth in the acclimatization o f micropropagated cuttings of helicônia (Heliconia lingulata Ruiz & Pavón cv. Fan .). The research consisted of three experiments, conducted in a high tunnel of forced culture at Emb rapa Tropical Agroindustry, located in Fortaleza, Ceará – Brazil (3º44 ' S and 38º33 ' W). The experimental design was a randomized blocks, with 4 treatments and 5 repetitions for the variables related to foliar development, and 5 treatments and 5 repetitions for the substratum. Four irrigation levels were analyzed in the first experiment: 1, 2, 3 and 4 mm of water. The pl ants cultivated in the substratum dust-of- coconut dry + wormcompost + soil, (1:1:1) in 180 cm 3 plastic containers, were irrigation twice a day. Five different combinations for substr atum were tested in the second experiment: 1:1:1 where S1 (dry coir dust + wormcompost + soil); S2 (green coir dust + vermiculite + compost of chicken bed); S3 (green coir dust + wormcompost + soil); S4 (dry coir dust + vermiculite + compost of chicken bed) and S 5 (Hortimix®). The plants, cultivated in the different substrate in 180 cm 3 plastic containers, were irrigated with a 3 mm wat er level twice a day. Four plastic containers types were evaluated in the third experiment: small cup (100 cm 3 ); small (180 cm 3 ); great plastic container (300 cm 3 ) and great cup (400 cm 3 ). The cuttings were cultivated with S 1 and they were irrigated with a 3 mm water level twice a day. The agronomics variable, evaluated in the experiments w ere: height of the plant, number leaf and stem diameter. In the first experiment the variable s were analyzed in 15 and 30 days after applications of water depth (DAL). For the othes ex periments the data were collected in 30, 60 and 75 days after the transplant (DAT). The resu lts of the experiments had evidenced that the best development of the cuttings of helicônia o ccurred when: cultivated in great plastic container of 300 cm 3 ; with substratum using the combination PCV+H+S and hortimix, and with water depth of 2,5 mm day -1.